The potential of agroecology to combat hunger in the developing world - Altieri, Miguel A.; Rosset, Peter M.; Thrupp, Lori Ann (International Food Policy Research Institute, 1998)
In this policy brief we argue that the agroecological approach to food production offers more hope of combating hunger in a sustainable fashion than does the more conventional "green revolution" strategy. While agroecological technology is suitable for small farmers, has positive impacts on equity and is environmentally friendly, the green revolution and similar approaches have caused serious land degradation and have accentuated rural inequity--the root cause of hunger.